Violence and Motherhood: Comparing the Influence of Physical and Psychological Abuse on Parenting Approaches - Austria, Genesis; Capito, Raymund; Espelita, Mark Moises (Journal of Interdisciplinary Perspectives, 2025)
Parenting approaches significantly influence children's developmental outcomes, yet understanding how violence against women impacts parenting remains critical. Existing research emphasizes the adverse effects of violence on familial dynamics but lacks a comparative analysis of physical and psychological violence in the Philippine context. This study addresses this gap by examining how these forms of violence influence the parenting approaches of women victims of abuse. The research employed a comparative descriptive design involving 50 women who sought care at the Dr. Jose N. Rodriguez Memorial Hospital and Sanitarium. Data were collected through validated questionnaires assessing parenting styles using a 4-point Likert scale. Respondents were categorized based on experiences of physical (21 participants) or psychological violence (29 participants). Physical violence included forms of assault such as hitting, punching, kicking, slapping, pushing, and shoving, while psychological violence encompassed manipulation, intimidation, and verbal abuse, including name-calling, shaming, and yelling. Key findings reveal that both forms of violence significantly shape parenting behaviors. Women exposed to physical violence tend to adopt stricter and more protective parenting styles, while psychological violence leads to heightened emotional vigilance and self-doubt. Psychological violence exhibited slightly more substantial impacts across dimensions, including emotional bonding, discipline, trust, and self-efficacy. Notably, respondents from both groups reported protective parenting behaviors and challenges with emotional connection. The study underscores the importance of trauma-informed interventions tailored to the distinct impacts of physical and psychological violence. These findings contribute to the development of evidence- based programs aimed at breaking cycles of violence and fostering healthier parent-child relationships in the Philippine context.